Sex Determination Using Fingerprint Ridge Density In South Indian Population - Sam, Nithin Mathew; P, Rema; Nair B , Venugopalan (Journal of Indian Academy of Forensic Medicine, 2015)
Determination of sex is vital in establishing the identity of human remains and has always been a  challenge for forensic pathologists, particularly when a fingerprint recovered from crime scene does not  match with any of those available in the records. The present study was conducted on 100 males and 100  females of South Indian Population, aged between 18 and 81 years, to study the possibility of  differentiation of gender using fingerprint ridge density. For calculating the finger print ridge density, the  upper portion of the radial border of each print was chosen and the epidermal ridges in a defined area  counted. Results show that women have a significantly higher fingerprint ridge density than men.  Application of Baye’s theorem suggests that a fingerprint having ridge density of 14/25mm2is more likely to be that of a female.  Discriminant analysis on the study data could derive formulae to predict the sex using fingerprint ridge  density. The results show that fingerprint ridge density can be used as a tool for sex determination.
Keywords: Fingerprint; Ridge density; Baye’s theorem; Discriminant analysis; Sex determination